Komunikasi Edukasi Penyuluhan Slow Deep Breathing Exercises Terhadap Hipertensi Pada Warga Kelurahan Sumber Surakarta di Wilayah Binaan Puskesmas Banyuanyar - Jihan Bariqa Arya Ramadhani; Arin Supriyadi; Selina Sinta Debi (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: High blood pressure, commonly known as hypertension, is a medical condition that must be taken seriously. If uncontrolled, hypertension can cause various complications from other serious diseases. Seeing the high prevalence of hypertension in Indonesia, efforts are needed to reduce blood pressure in elderly people who suffer from hypertension. The aim of this activity is to provide educational outreach about hypertension, namely a slow deep breathing exercise training program to help lower blood pressure in residents suffering from hypertension.Method: Community Service Counseling is carried out using leaflets, blood pressure checks using a sphygmomanometer and blood pressure lowering exercises using the slow deep breathing exercise technique. The population for this activity are residents of the Sumber Surakarta subdistrict.Results: One effective treatment method for patients with hypertension is slow deep breathing exercises. This community service activity was held at Posyandu Posyandu COE Catur Manunggal RW 16 Sumber. Conclusion: The outreach and education activities on slow deep breathing exercises for hypertension carried out at Posyandu COE Catur Manunggal RW 16 Sumber Village, can increase the knowledge of cadres and residents about hypertension and slow deep breathing breathing exercises. The results are expected to bring improvements to the quality of life of residents suffering from hypertension